THE USE OF THE FSMU METHOD AND ITS IMPORTANCE IN IMPROVING GENETIC KNOWLEDGE IN THE EDUCATIONAL PROCESS - Mirzoeva M.A. (Bright Mind Publishing, 2025)
This article provides information on effective methods of undergraduate education, on the introduction of new mechanisms for teaching genetics as a science. At the present stage of development, attention to the development of new modern pedagogical technologies in higher education has increased even more, one of the main goals was to improve the quality of the lesson, bringing it to the level of world patterns. The "FSMU method" is used in solving controversial issues, as well as in conducting a debatable learning process, since this technology allows students to defend their opinions, think freely, express their personal opinions to others, openly argue and at the same time teaches a culture of argumentation. In the future, the main attention will be paid to the possibilities of wider application of these approaches in teaching genetics courses, greater attention to the practice of genetics as a science, and the use of new methods for assessing student academic performance.
Keywords: competence, model, accreditation, multidisciplinary, knowledge, skills, pedagogical technology, FSMU, chromosome, technology, gender, autosomes, heterogamete, homogamete. active learning, artificial intelligence, learning, learning practice.